SI/IT Strategic Planning Using Ward and Peppard Method on Secretariat of Salatiga City Regional People's Representative Council - Mella Cahaya Nugraha; Augie David Manuputty (Journal of Information System and Informatics, 2022)
Secretariat of Salatiga City Regional People's Representative Council is a regional apparatus that has the task of assisting the implementation of the functions and duties of the Regional Government. Secretariat of Salatiga City Regional People's Representative Council has also played an active role in implementing information systems in its business processes, but the use of existing information systems has not been maximized. Its cause performance has not run effectively and efficiently. Therefore, it is necessary to plan a good information system strategic planning. In this research using the Ward and Peppard method starting from conducting a SWOT analysis to find out the weaknesses and strengths of the organization eventually it can face threats from outside the organization, Value Chain Analysis, and business strategy recommendations. This research will produce an application portfolio in the form of a McFarlan Strategic Grid, which will describe the information system needs that will become an information system strategic planning that will be implemented within 3 years.